The Religious Roles of Muslimah Influencers in the Construction of Contemporary Families - Petriani, Deala Rosyida (USRATY : Journal of Islamic Family Law, 2025)
This study aims to examine the social and religious roles of Muslimah influencers in shaping the values, norms, and behaviors of contemporary Muslim families, particularly within the context of rising digital religiosity and increasing reliance on social media as a source of life guidance. The central research question addresses how Muslimah influencers contribute to the construction of the ideal modern family among Muslim communities. The novelty of this study lies in its emphasis on gender-based religious authority in digital spaces—an aspect that remains underexplored in Islamic family discourse. Employing a qualitative approach through digital ethnography and content analysis of selected Muslimah influencers' platforms (YouTube, Instagram, and TikTok), this research explores how religious messages, lifestyle narratives, and visual representations serve as tools for disseminating models of piety, gender roles, and family ethics. The findings reveal that Muslimah influencers act as cultural agents who bridge traditional Islamic teachings with modern lifestyles and actively shape new family values through aspirational content that highlights simplicity, emotional sensitivity, and spiritual motherhood. In conclusion, these influencers play a significant role in popularizing new forms of religious authority and redefining the ideal Muslim family in the digital era. The academic contribution of this study lies in offering new insights into the relationship between gender, religious authority, and the transformation of family values within modern Muslim societies.